2006
DOI: 10.1111/j.0038-4941.2006.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and the Digital Divide: The Roles of Structural Conduciveness and Global Connection in Internet Diffusion*

Abstract: Objectives. The goal of this research is to examine the role of modernization (i.e., structural conduciveness) in the form of income, telephone price and structure, education, and political structures, and global contact in the form of world cities, trade, investment, activities of international nongovernmental organizations, and short-term exchanges of population in driving the worldwide diffusion of the Internet. Methods. We use longitudinal regression analyses (1995)(1996)(1997)(1998)(1999)(2000) of change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 21 publications
3
60
1
3
Order By: Relevance
“…This is mostly due to practical and economic reasons. Studies such as Xiaoming and Kay (2004) and Crenshaw and Robison (2006) have found urban population to have a significant impact on Internet diffusion.…”
Section: Location Of Aeasmentioning
confidence: 99%
“…This is mostly due to practical and economic reasons. Studies such as Xiaoming and Kay (2004) and Crenshaw and Robison (2006) have found urban population to have a significant impact on Internet diffusion.…”
Section: Location Of Aeasmentioning
confidence: 99%
“…Therefore, it is plausible to assume that countries in which people tend to live in cities benefit from higher penetration rates. Studies such as Kay and Xiaoming (2004) and Crenshaw and Robison (2006) have found urban population to have a significant impact on Internet diffusion.…”
Section: Internet Diffusion Ratesmentioning
confidence: 99%
“…Guillen and Suarez (2004) extend previous research by showing that regulatory, political, and sociological variables are also responsible for some of the difference in penetration rates across countries. Crenshaw and Robison (2006) analyze the main factors contributing to the change in the number of Internet hosts for approximately 80 countries from 1995 to 2000. They employ numerous measures of globalization to determine whether a country's openness has a positive impact on Internet growth.…”
mentioning
confidence: 99%
“…No entanto, Barzilai-Nahon (2006) (BILLON et al, 2007). Assim, um maior grau de difusão das TIC é esperado em regiões com maior proporção de população urbana (CRENSHAW; ROBISON, 2006;SAN, 2006).…”
Section: Indicadoresunclassified
“…Da mesma forma que a classe social, o grau de instrução também demonstrou ser de grande importância na determinação das quatro variáveis dependentes analisadas, com um aumento da probabilidade de adoção para graus de instrução mais elevados, indo de acordo com o esperado por diversos estudos anteriores (CRENSHAW; ROBISON, 2006;HARGITTAI, 1999;VICENTE e LÓPEZ, 2006;Billon et al, 2007).…”
Section: Grau De Instruçãounclassified